 Reasoning Inequalities Questions for SBI PO 2019 | Download Inequalities Questions PDF at Smartkeeda  Directions: In these questions, relationship between different elements is shown in the various statements which is followed by three conclusions. Choose the correct answer on the basis of information given below.
Important for :
1
Statements:  M ≥ S ,   K < A,   S = T,   A > Y,   K > M,   Y ≤ O,   T ≥ E

Conclusions: M > E,   M = E,   O > S
» Explain it
D
Statements:  M ≥ S , K < A, S = T, A > Y, K > M, Y ≤ O, T ≥ E

Conclusions: (I) M > E   (II) M = E   (III) O > S

By combining all the statements, we get the following equation:

≥ Y < A > K > M ≥ S = T ≥ E

For conclusion (I): M > E

Here, the common sign between M and E is '≥'. Thus M ≥ E.

Hence conclusion (I) does not follow individually.

For conclusion (II): M = E

Here, the common sign between M and E is '≥'. Thus M ≥ E.

Thus conclusion (II) does not follow individually.

On combining conclusions I and II we get "M ≥ E".

Therefore either conclusion (I) or (II) follows.

For conclusion (III): O > S

Here we can see the opposite signs between O and S, thus no relationship can be established between them.

Therefore conclusion (III) does not follow.

Hence option D is correct.
2
Statements:  A < B, C = D,   E < F,   B > D,   G ≥ C,   A > F,   H = E

Conclusions: G > B    A > H    C = H
» Explain it
C
Statements:  A < B, C = D , E < F, B > D, G ≥ C, A > F, H = E

Conclusions:  G > B    A > H    C = H

By combining all the statements, we get the following equation:

G ≥ C = D < B > A > F > E = H

For conclusion (I): G > B

Here we can see the opposite signs between G and B, thus no relationship can be established between them.

Hence conclusion (I) does not follow.

For conclusion (II): A > H

Here, the common sign between A and H is '>'. Thus A > H.

Thus conclusion (II) follows.

For conclusion (III): C = H

Here we can see the opposite signs between C and H, thus no relationship can be established between them.

Therefore conclusion (III) does not follow.

Hence option C is correct.

3
Statements:  S < U,    N ≥ V,   U = Q,   R > N,   S ≤ G,   Q > T,    V = G

Conclusions:  U > T    R > S    R = S
» Explain it
B
Statements:  S < U, N ≥ V, U = Q, R > N, S ≤ G, Q > T, V = G

Conclusions:  U > T    R > S    R = S

By combining all the statements, we get the following equation:

R > N ≥ V = G ≥ S < U = Q > T

For conclusion (I): U > T

Here, the common sign between U and T is '>'. Thus U > T.

Hence conclusion (I) follows.

For conclusion (II): R > S

Here, the common sign between R and S is '>'. Thus R > S.

Thus conclusion (II) follows.

For conclusion (III): R = S

Here, the common sign between R and S is '>'. Thus R > S.

Therefore conclusion (III) does not follow.

Hence option B is correct.

4
Statements:  M ≥ P,   U < K,   K < A,   G = J,   P < U,   G > A

Conclusions:  P < G       J > K     U < G
» Explain it
E
Statements:  M ≥ P, U < K, K < A, G = J, P < U, G > A

Conclusions:  P < G     J > K    U < G

By combining all the statements, we get the following equation:

M ≥ P < U < K < A < G = J

For conclusion (I): P < G

Here, the common sign between P and G is '<'. Thus P < G.

Hence conclusion (I) follows.

For conclusion (II): J > K

Here, the common sign between K and J is '<'. Thus K < J or J > K.

Thus conclusion (II) follows.

For conclusion (III): U < G

Here, the common sign between U and G is '<'. Thus U < G.

Therefore conclusion (III) follows.

Hence option E is correct.

5
Statements:  B < A,   G = H,   O > A,   H < I,   J = I,   G < O

Conclusions:  J > A     B > H    I < O
» Explain it
E
Statements:  B < A, G = H, O > A, H < I, J = I, G < O

Conclusions:  J > A    B > H   I < O

By combining all the statements, we get the following equation:

J = I > H = G < O > A > B

For conclusion (I): J > A

Here we can see opposite sign between J and A, thus no relationship can be established between them.

Hence conclusion (I) does not follow.

For conclusion (II): B > H

Here we can see opposite sign between B and H, thus no relationship can be established between them.

Thus conclusion (II) does not follow.

For conclusion (III): I < O

Here we can see opposite sign between I and O, thus no relationship can be established between them.

Therefore conclusion (III) does not follow.

Hence option E is correct.